Does corruption matter for stock markets? The role of heterogeneous institutions - Lakshmi, Geeta; Saha, Shrabani; Bhattarai, Keshab (Economic Modelling, 2021)
In examining the role of institutions in resisting corruption and its impact on growth, most studies concentrate on the aggregate level and conclude that sound institutions enhance growth. We focus instead on varying dimensions of heterogeneous institutions in the presence of corruption and their interactive effect on stock returns in four emerging economies: Brazil, Russia, India, and China (BRIC). We pay particular attention to democratic accountability, bureaucratic quality, and law and order. Using monthly data for the first time in this literature, we find that corruption and other weaker institutions lower stock returns during the period 1995-2014. However, interaction effects show interesting mixed results: Bureaucratic quality can mitigate the ill effects of corruption and increase returns by reducing red tape, whereas corruption distorts law and order and lowers stock returns. Our findings suggest that policies to enhance bureaucratic efficiency can abate the adverse effects of corruption, but a restrictive law and order environment tends to lower stock returns.
Keywords: Institutions; Stock returns; BRIC countries; Growth; Corruption